Overcoming obstacles to peace : local factors in nation-building - Dobbins, James, 1942- (Rand Corporation monograph series., 2013)
"This volume analyzes the impediments that local conditions pose to successful outcomes of nation-building interventions in conflict-affected areas. Previous RAND studies of nation-building focused on external interveners' activities. This volume shifts the focus to internal circumstances, first identifying the conditions that gave rise to conflicts or threatened to perpetuate them, and then determining how external and local actors were able to modify or work around them to promote enduring peace. It examines in depth six varied societies: Cambodia, El Salvador, Bosnia and Herzegovina, East Timor, Sierra Leone, and the Democratic Republic of the Congo. It then analyzes a larger set of 20 major post-Cold War nation-building interventions. The authors assess the risk of renewed conflict at the onset of the interventions and subsequent progress along five dimensions: security, democratization, government effectiveness, economic growth, and human development. They find that transformation of many of the specific conditions that gave rise to or fueled conflict often is not feasible in the time frame of nation-building operations but that such transformation has not proven essential to achieving the primary goal of nation-building -- establishing peace. Most interventions in the past 25 years have led to enduring peace, as well as some degree of improvement in the other dimensions assessed. The findings suggest the importance of setting realistic expectations -- neither expecting nation-building operations to quickly lift countries out of poverty and create liberal democracies, nor being swayed by a negative stereotype of nation-building that does not recognize its signal achievements in the great majority of cases."--Page 4 of cover.